Understanding Human Decision Making in an Interactive Landslide Simulator Tool via Reinforcement Learning - Chaturvedi, Pratik; Dutt, Varun (Frontiers in Psychology, 2021)
Prior research has used an Interactive Landslide Simulator (ILS) tool to investigate human decision-making against landslide risks. It has been found that repeated feedback in ILS tool about damages due to landslides causes an improvement in human decisions against landslide risks. However, little is known on how theories of learning from feedback (e.g., reinforcement learning) would account for human decisions in the ILS tool. The primary goal of this paper is to account for human decisions in the ILS tool via computational models based upon reinforcement learning and to investigate the underlying cognitive processes involved when people make decisions in the ILS tool. Four different reinforcement-learning models were developed and evaluated in their ability in capturing human decisions in an experiment involving two conditions in the ILS tool. The parameters of an Expectancy-Valence (EV) model, two Prospect-Valence-Learning models (PVL and PVL-2), a combination EV-PU model, and a random model were calibrated to human decisions in the ILS tool across the two conditions. Later, different models with their calibrated parameters were generalized to data collected in an experiment involving a new condition in ILS. When generalized to this new condition, the PVL-2 model’s parameters of both damage-feedback conditions outperformed all other RL models (including the random model). We highlight the implications of our results for decision-making against landslide risks.